Source apportionment of the light absorbing impurities present in surface snow of the India Western Himalayan glaciers. (1st February 2021) - Thind, Parteek Singh; Kumar, Deepak; John, Siby
Abstract: Darkening of surface snow caused by deposition of the Light absorbing impurities (LAIs) can reduce its albedo and further enhance its melting. Early melting of surface snow leads to exposing the underneath ice mass to sunlight for longer duration and consequent retreat of glaciers. This retreat of glaciers, further cause several hydrological and climatic implications. In this study, efforts were made to perform source apportionment of the LAIs found in the surface snow samples, collected from the three glaciers located in the Indian Western Himalayas (IWHs). Ionic composition of the snow samples derived from ion chromatography was further analyzed using two receptor models viz., principal component analysis (PCA) and positive matrix factorization (PMF). It was observed that biomass burning, vehicular emissions, dust emissions and coal combustion were the major sources of the LAIs in the IWHs. The PMF analysis, estimated that biomass burning and vehicular emissions contributed ~30% each in the emission of the LAIs. Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT)-based back trajectories for 7-days were plotted to identify locations of the sources of the LAIs. Back trajectories were observed to pass through agricultural, forest-covered and urban areas. The observations made, during this study, would help local authorities in identifying the hot spots of the LAIs'-emissions, on the basis of which region-specific policies could be framed to mitigate the anthropogenic emissions of the LAIs. Graphical abstract: Image 1 Highlights: Snow from Indian Western Himalayas was analyzed for source apportionment of LAIs. Ionic composition of snow samples was analyzed using PCA and PMF receptor models. Major sources, of the LAIs, identified were biomass burning and vehicular emissions. HYSPLIT identified the sources' location in agricultural, forest and urban areas.